The causative pathogen determines the inflammatory profile in cerebrospinal fluid and outcome in patients with bacterial meningitis - Grandgirard, Denis; Gäumann, Rahel; Coulibaly, Boubacar; Dangy, Jean-Pierre; Sié, Ali; Junghanss, Thomas; Schudel, Hans; Pluschke, Gerd; Leib, Stephen L. (Mediators of inflammation, 2013)
Background. The brain’s inflammatory response to the infecting pathogen determines the outcome of bacterial meningitis (BM), for example, the associated mortality and the extent of brain injury. The inflammatory cascade is initiated by the presence of bacteria in the cerebrospinal fluid (CSF) activating resident immune cells and leading to the influx of blood derived leukocytes. To elucidate the pathomechanisms behind the observed difference in outcome between different pathogens, we compared the inflammatory profile in the CSF of patients with BM caused by Streptococcus pneumonia ( ), Neisseria meningitidis ( ), and Haemophilus influenza ( ). Methods. CSF inflammatory parameters, including cytokines and chemokines, MMP-9, and nitric oxide synthase activity, were assessed in a cohort of patients with BM from Burkina Faso. Results. Pneumococcal meningitis was associated with significantly higher CSF concentrations of IFN-γ, MCP-1, and the matrix-metalloproteinase (MMP-) 9. In patients with a fatal outcome, levels of TNF-α, IL-1β, IL-1RA, IL-6, and TGF-α were significantly higher. Conclusion. The signature of pro- and anti-inflammatory mediators and the intensity of inflammatory processes in CSF are determined by the bacterial pathogen causing bacterial meningitis with pneumococcal meningitis being associated with a higher case fatality rate than meningitis caused by N. meningitidis or H. influenzae.